A Comparative Perspective of “Engaged Buddhism” and “Renjian Fojiao” (“Humanistic Buddhism”) in Chinese Speaking Discourse: Exclusivism, Inclusivism, or Pragmatism? - Krause, Carsten (Religions, 2024)
The two modern concepts, “Engaged Buddhism” and renjian fojiao 人間佛教, with the variety of its English translations (such as “Humanistic Buddhism”), were developed and discussed with and without reference to each other over several decades. This article raises the question of how “Engaged Buddhism” has been portrayed in the Chinese-speaking world. It therefore reflects on a hybrid conceptual history and distinguishes between “concept-unaffected” and “concept-affected” (“concept-affirming”, “concept-negating”, and “concept-corresponding”) positionings in the Buddhist world, as well as a “concept-distancing” and “concept-processing” scholarship of Buddhist studies. The concept of “Engaged Buddhism” has been rendered with various Chinese terms in mainland China and Taiwan, e.g., “rushi fojiao” 入世佛教 (Buddhism that Enters the World), “canyu fojiao” 參與佛教 (Participatory Buddhism), and “zuoyi fojiao” 左翼佛教 (Left-Wing Buddhism). As can be seen from a rich body of sources, its discussion among Chinese-speaking Buddhists and scholars increased over the past twenty years and has been strongly characterized by comparisons with “renjian fojiao”, which can lead to different currents, such as exclusivism, inclusivism, and pragmatism.